2014
DOI: 10.4028/www.scientific.net/amm.575.78
|View full text |Cite
|
Sign up to set email alerts
|

Feedstock Characterization of Elemental Nickel and Titanium Powders Mixture for Metal Injection Moulding Process

Abstract: The success of metal injection moulding (MIM) process is significantly influenced by the homogeneity level of the powder-binder mixture (feedstock). This paper highlights some initial characterization of the feedstock containing elemental Ni and Ti powders mixture, (50.8 at.% Ni/ 49.2 at.% Ti) mixed with Palm stearin-based binder system. The feedstock was prepared using an internal mixer, HAAKE Rheomix at a temperature of 160°C for 2 hours. The feedstock was then characterized by Differential Scanning Calorime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…From the graph, it shows that the range of n value for the feedstock in the range of 0.48 to 0.57 for powder loading 65.5vol% while 0.43 to 0.52 for powder loading 67.5vol%. Compare to the previous research conducted by Ismail and Razali where the n value is within the range of 0.698 to 0.721 [4] while 0.5 to 0.7 [3]. It is demonstrated that the the shear rate had moderately affected by the viscosity of the feedstock which is good for moulding process in order to avoid binder separation [9].…”
Section: Shear Sensitivity Index (N)contrasting
confidence: 46%
See 1 more Smart Citation
“…From the graph, it shows that the range of n value for the feedstock in the range of 0.48 to 0.57 for powder loading 65.5vol% while 0.43 to 0.52 for powder loading 67.5vol%. Compare to the previous research conducted by Ismail and Razali where the n value is within the range of 0.698 to 0.721 [4] while 0.5 to 0.7 [3]. It is demonstrated that the the shear rate had moderately affected by the viscosity of the feedstock which is good for moulding process in order to avoid binder separation [9].…”
Section: Shear Sensitivity Index (N)contrasting
confidence: 46%
“…Previous study of NiTi done by Ismail [3] and Razali [4] which used nickel and titanium as starting elemental powders and both powders exhibit spherical shape. Moreover, the PEG and PMMA binders were used by Ismail while PS and PE were used by Razali respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Two atomic ratios of Ni-Ti were investigated; 50-50 and 50.8-49.2 and the powder loading was kept 65.5 vol %. The elemental powders were blended using a stainless steel ball mill for 4 hours with a ball-to-powder ratio of 2:1 to ensure uniform powder distribution [8]. The binder system comprised of palm stearin (PS) and polyethylene (PE) with a weight fraction of 60-40 based on the previous successful work [8].…”
Section: Methodsmentioning
confidence: 99%
“…The elemental powders were blended using a stainless steel ball mill for 4 hours with a ball-to-powder ratio of 2:1 to ensure uniform powder distribution [8]. The binder system comprised of palm stearin (PS) and polyethylene (PE) with a weight fraction of 60-40 based on the previous successful work [8]. The as-mixed powders were then mixed with the binder system using an internal mixer, HAAKE Rheomix at 160 o C with rotational speed of 50 rpm for 3 h until a homogenous mixture was observed [8].…”
Section: Methodsmentioning
confidence: 99%
“…2 in terms of log shear viscosity (η) versus log shear rate (γ) based on Equation 1. Razali et al (2014) reported the melting point of the backbone binder; PE is about 100°C. Hence, the temperature of rheological test was tested in the range of 130°C to 170°C (>100°C) based on the mixing process temperature.…”
Section: Rheological Characterization and Injection Moldingmentioning
confidence: 99%